Radiosurgery for intracranial meningiomas: A systematic review and meta-analysis. (May 2017) - Pinzi, Valentina; Biagioli, Elena; Roberto, Anna; Galli, Francesca; Rizzi, Michele; Chiappa, Federica; Brenna, Greta; Fariselli, Laura; Floriani, Irene
Highlights: This paper focuses on radiosurgery for grade I–II meningioma. A systematic review of available literature was performed. Meta-analysis on symptom control and toxicity was carried out. Structured information on treatment-related outcomes was obtained. Abstract: Background: Radiosurgery(RS), both in single and multiple sessions, have been performed for intracranial meningiomas. Different aspects are still controversial on this field. The aim of this systematic review is to summarize the current literature on long-term efficacy and safety of RS for meningiomas. Methods: Online databases were searched for studies published until April 2015. The primary outcomes were disease control and progression-free-survival(PFS). The secondary outcomes were symptom control and radiation-induced toxicity. Results: The estimate of disease control rate ranged from 87.0% to 100.0% at 5 years and from 67.0% to 100.0% at 10 years. The PFS rate ranged 78.0%–98.9% and 53.1%–97.2% at 5 and 10 years, respectively. The overall symptom control was 92.3%, the overall toxicity was 8.1%. Conclusions: RS can be considered a safe and effective treatment. Efforts are needed in standardizing the definition of local and symptom control and toxicity in order to properly compare different treatment schedules.